A locating diagnosis of partial discharge on cross-bonding ground system - Inwanna, W.; Mongkolsatitpong, S.; Chancharoensook, P.; Pattanadech, N. (My University, 2021)
At the present, Thailand has turned the attention to Underground Cable (UC) systems and trends to use it more to safety, stability and reliability of electrical system. However, one problem that can affect to this electrical system is the Partial Discharge (PD) problem. Most of PD problems are caused by incomplete installation, maintenance reason and insulation degradation on the weakest part, especially cable joint. This paper proposes a method of analysis to locate the PD source in UC systems with Cross Bonding (CB) focus on cable joints. This work has carried out in laboratory on CB system model using 50ohm R58 coaxial cable instead of underground cable. The PD detection technique according to IEEE 400.3 standard with a RFCT sensor to refer the appropriate signal. This work uses a PD diagnostic device that can filter noise from the PD groups and separate groups of PD for greater analysis accuracy. To determine which cable joint is PD source and to be able to fix it on the spot. The PD signal analysis are performed by using time of arrival method considered together with the characteristics and the polarity of the PD pulse.
Keywords: Cable joint; Cross-bonding; Partial discharge; PD location; Underground cable